Analisis Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Wisatawan Di Pusat Oleh-Oleh Sun Osing Beach Banyuwangi - Afrida Ermawati, Eka; Putri, Selviana; Yustita, Aprilia Divi (Sadar Wisata: Jurnal Pariwisata, 2023)
The act when someone pay to get a certain product known as purchase decision. Purchase decisions are influenced by various factors, including brand image and product quality. The aims of this study was to analize the influence of brand image and product quality toward the decision made to buy at Sun Osing Beach Souvenir Center. The type of research applied in this study is a quantitative associative research. The sampling technique used nonprobability sampling with 50 respondents. The research data processing used a statistical test tool, SPSS version 24. The results of data analized picture that partially brand image variable has a significant effect on purchasing decisions. On the other side, product quality variable does not have a significant effect on purchasing decisions. Meanwhile, the simultaneous test analysis shows that brand image and product quality have a simultaneous influence tourists purchasing decisions at Sun Osing Beach Souvenir Center